(untitled) (Acta Scientiarum. Biological Sciences, 2024)
This study delves into the intricate relationship between women and medicinal plants, underscoring their historical and cultural roles mainly in 11 different countries. By specifically examining the impact of social impositions on gender in healthcare and the use of medicinal plants, the research critiques the perspectives that have marginalized both women and nature. To address these issues, ethnobotanical studies should promote research that encompasses the gender. Conducting a systematic review on Women and Medicinal Plants, the research explores key aspects in ethnobotanical studies: botanical knowledge, transmission of knowledge, medicinal plants used in women’s reproductive health, access to healthcare, and the primary knowledge holders. The bibliographic survey, utilizing the Capes database, reveals 205 plant species with 32 medicinal uses for women’s health. Rute chalepensis L. (rue) was mentioned four times for abortion, labor contraction, facilitating childbirth, and placental expulsion. In relation to women’s reproductive health, different plants have been used by women and traditional practitioners worldwide. The use of medicinal plants can be associated with social vulnerability in marginalized communities by society which do not have easy access to public health, so they rely on alternative methods such as homemade remedies. Although knowledge about medicinal plants is an intellectual task developed by women, in some societies, such as capitalist societies, gender roles will evolve into specific knowledge, such as the task of family health care. The triple workload is not beneficial to women. Traditional knowledge, when allied with sustainability, can promote gender equality by transmitting intergenerational botanical knowledge without gender distinction and by reclaiming cultivation practices beneficial to the environment, biodiversity, and human health. The study invites ethnobotanical researchers to investigate gender dynamics within their studies. The results of this work can contribute to future research on women and medicinal plants.